Detection of albendazole resistant gastro-intestinal nematodes in village cattle of south-eastern Mali - Mungube, E.O.; Rexa, F.; Hinney, B.; Sanogo, Y.; Diall, O.; Randolph, Thomas F.; Clausen, Peter-Henning (2012)
To acquire information on gastro-intestinal nematodes in village cattle and their current control strategy in south-east Mali, repeated faecal samplings and examination for faecal egg counts (FECs) on risk group cattle were conducted between November 2008 and November 2009. A strategic helminth control strategy was tested for its effectiveness in controlling helminths. This was undertaken on risk group cattle that were randomly divided into an albendazole treated and untreated control with the latter getting treated with 10 mg/kg of albendazole sourced from Malian markets at the start and end of rainy season and the former receiving a placebo. A faecal egg reduction test was conducted in November 2009 where all the albendazole treated calves were further split into two groups before one group was treated with 10 mg/kg of albendazole from Mali and the other with albendazole from Germany. The control group still received a placebo. Faecal egg counts were compared at day 0 (treatment day) and day 14 post-treatment. Larval cultures were carried out on faecal samples from the albendazole treated and control groups to determine the helminth ecology. Young animals and zebu cattle were associated with higher faecal egg counts. Although breed and sex were not significantly associated (p>0.05) with FECs, the time when the study was conducted highly (p<0.0001) influenced FECs. The faecal egg count reduction test (FECRT) results showed that albendazole from Malian markets had a faecal egg reduction of 55.6% while that from Germany had faecal egg count reduction (FECR) of 79.3%. The low FECRT indicative of gastro-intestinal nematode (GIN) resistance against albendazole warrants further investigation before concluding that such resistance does exist.